Philippines : Reform of the Fiscal Regimes for Mining and Petroleum. (IMF Staff Country Reports; Country Report ;, 2012)
This Technical Assistance (TA) Report on the Philippines discusses the fiscal regime for the mining sector. The Philippines has long been a producer of minerals, but the mining and petroleum sectors account for only a small share of the economy, exports, and government revenue. The petroleum sector comprises only two fields-one producing natural gas and condensate and one producing crude oil. The TA report suggests legislative reforms of financial and technical assistance agreements (FTAAs), repealing of tax incentives and consolidating all domestic tax rules, and fostering sound environmental practices.